Evaluation of breeding value based on body weight and body measurement at one day of age in Madura cattle - Zulfaini Shamad; Kuswati Kuswati; Ahmad Furqon; Priyo Sugeng Winarto; Agus Susilo; Veronica Margareta Ani Nurgiartiningsih (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
The objective of this research was to evaluate the breeding value based on body weight and body measurement at one day of age in Madura cattle on the Technical Implementation Unit of Animal Breeding and Health East Java. Recording data used were withered height (WH), body length (BL), chest girth (CG), and birth weight (BW) that birth from 2014 until 2020.  Analyzed variables consist of heritability, breeding value, and spearman correlation. The analysis result showed heritability for the performance of 1 day of age in Madura cattle categorized as a medium until high (0.33 – 0.64). Breeding value from 10 bull based on BW was 60% categorized positive. Meanwhile, breeding value based on WH, BL, CG was 40% categorized positive. The Spearman correlation of BW with WH and CG had a high correlation (0.73 and 0.78), while BW and BL had a low correlation (0.22). This research concluded that the highest breeding value of body weight and body measurement of Madura cattle at 1 day was sire Montahai/1661100. The genetic potency of Madura cattle should be improved by applying for a consistent breeding program with a sound recording and selection program.